Socio-economic correlates of more than one personal account ownership in the Kumasi Metropolis of Ghana - Bawuah, Jonas; Yusheng, Kong; K. Jerry Asare, Isaac; Osei Owusu, Stella (International Journal of Accounting and Economics Studies, 2019)
Financial inclusion is seen as one of the major tools that can be used to oust poverty. Given this, several studies have been done to find out the kind of individuals who are likely to have indicators of financial inclusion such as ownership of savings accounts among others. However, it has been observed that certain individuals tend to have multiple savings accounts in which very little is known in the literature about the features of such individuals and why. This study therefore purposively sampled 200 adult respondents in the Kumasi Metropolis of Ghana with at least one account in any formal institution, in order to investigate the determinants of more than one or multiple personal financial accounts holding. The study employed the binary logit model as the empirical estimation technique. The study therefore found that, most respondents chose enjoyment of several benefits as the most important reason they own more than one personal account. From the regression estimates, the study revealed males, those aged 31-40 years, the employed, married, respondents with junior high school (J.H.S), senior high school (S.H.S) and tertiary levels of education to be more likely to own more than one personal account. The findings therefore fill a major gap in the financial inclusion literature and hence further reinforce the essence of socio-economic factors such as gender, age, education, employment, religion and marital status in the financial inclusion drive.Â Â Â
Keywords: Financial Inclusion; More Than One or Multiple Accounts Ownership; Ghana.